2021
DOI: 10.15560/17.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Symphyotrichum subulatum (Michx.) G.L.Nesom (Asteraceae): a new distribution record of an alien plant species in Kashmir Himalaya, India

Abstract: Symphyotrichum subulatum (Michx.) G.L.Nesom (Asteraceae) is reported as a new alien plant record for Kashmir Himalaya. The taxonomic identification of species is confirmed on the basis of shape of involucre, floral and seed characters. Detailed description, distribution map, and comments on distribution and ecology are also provided along with photographic illustration to facilitate easy identification of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…New distribution records in global biodiversity hotspots, such as the Himalaya, are important in meeting the Wallacean shortfall in biodiversity science (Gulzar et al 2021). Our new record of Pedicularis gracilis var.…”
Section: Discussionmentioning
confidence: 99%
“…New distribution records in global biodiversity hotspots, such as the Himalaya, are important in meeting the Wallacean shortfall in biodiversity science (Gulzar et al 2021). Our new record of Pedicularis gracilis var.…”
Section: Discussionmentioning
confidence: 99%
“…Due to extreme climate and limited accessibility, these cold regions were considered as little impacted by the problem of biological invasions Frenot et al 2005). However, recently many studies revealed the redistribution of the alien plant species in cold mountain regions (Morozova et al 2021;Gulzar et al 2021;Zargar et al 2021;Zargar et al 2023a). During recent oristic surveys in Ladakh, Trans-Himalaya, we have collected specimens of Matricaria discoidea DC.…”
Section: Introductionmentioning
confidence: 99%